How does climate exacerbate root causes of conflict in Uganda? An econometric analysis - Tirkaso, Wondmagegn; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Uganda, using a two-stage econometric approach. The findings show that climate shocks negatively affect household’s food security status (manly through temperature anomaly), and that food security variables significantly impact the probability of conflict incidence.